Early discoid lupus erythematosus protects against renal disease in patients with systemic lupus erythematosus: longitudinal data from a large Latin American cohort. (January 2017) - Pons-Estel, G J; Aspey, L D; Bao, G; Pons-Estel, B A; Wojdyla, D; Saurit, V; Alvarellos, A; Caeiro, F; Haye Salinas, M J; Sato, E I; Soriano, E R; Costallat, L T L; et al.
Objectives: The objective of this study was to examine whether early discoid lupus erythematosus (DLE) would be a protective factor for further lupus nephritis in patients with systemic lupus erythematosus (SLE). Methods: We studied SLE patients from GLADEL, an inception longitudinal cohort from nine Latin American countries. The main predictor was DLE onset, which was defined as physician-documented DLE at SLE diagnosis. The outcome was time from the diagnosis of SLE to new lupus nephritis. Univariate and multivariate survival analyses were conducted to examine the association of DLE onset with time to lupus nephritis. Results: Among 845 GLADEL patients, 204 (24.1%) developed lupus nephritis after SLE diagnosis. Of them, 10 (4.9%) had DLE onset, compared to 83 (12.9%) in the group of 641 patients that remained free of lupus nephritis (hazard ratio 0.39; P  = 0.0033). The cumulative proportion of lupus nephritis at 1 and 5 years since SLE diagnosis was 6% and 14%, respectively, in the DLE onset group, compared to 14% and 29% in those without DLE ( P  = 0.0023). DLE onset was independently associated with a lower risk of lupus nephritis, after controlling for sociodemographic factors and disease severity at diagnosis (hazard ratio 0.38; 95% confidence interval 0.20–0.71). Conclusions: Our data indicate that DLE onset reduces the risk of further lupus nephritis in patients with SLE, independently of other factors such as age, ethnicity, disease activity, and organ damage. These findings have relevant prognosis implications for SLE patients and their clinicians. Further studies are warranted to unravel the biological and environmental pathways associated with the protective role of DLE against renal disease in patients with SLE.